If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + -6) + -2x = 32 Reorder the terms: 3(-6 + x) + -2x = 32 (-6 * 3 + x * 3) + -2x = 32 (-18 + 3x) + -2x = 32 Combine like terms: 3x + -2x = 1x -18 + 1x = 32 Solving -18 + 1x = 32 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '18' to each side of the equation. -18 + 18 + 1x = 32 + 18 Combine like terms: -18 + 18 = 0 0 + 1x = 32 + 18 1x = 32 + 18 Combine like terms: 32 + 18 = 50 1x = 50 Divide each side by '1'. x = 50 Simplifying x = 50
| 1/3√9x | | 2(4-3x)=68 | | m^2-12m+69=0 | | 35g-13=-103 | | 6*x^3-9=0 | | 6x^2-40+x=0 | | 6*x^5-9=0 | | 2u+5=-3 | | f(x)=(0.7x+6)(0.4x-8) | | 2(3x-4)=(4x+3) | | x+5=2(5x-2) | | 2(x-5)-21=0 | | 7=6(x+6)+8x | | -27=-7+4v | | 4=-7/2•5 | | 3(2x+10)=40 | | (-6x/4)=5 | | 10x+10=12x-6 | | 2+1.25=10-2.75x | | 4(7+5)=16 | | 2x-10y(-4)=20 | | x^2-5y^2+4x-10y+4=0 | | v^2-10v-96=0 | | (-27x^3)(y)/(9x^4)(y) | | 2(2g+3)=38 | | 2x-2y+5z-2x-y+3z= | | 5cosx+6cosx-8=0 | | 3^14k7/2^19 | | 2(3x+1)=4(x+5) | | P^2+20p-3500=0 | | 5(2+1)=50 | | 0.71428571y-15=5y+30 |